Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1021/ic9017568
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Modes of Multidentate Ligands infac-[Re(CO)3(polyaminocarboxylate)] Analogues of99mTc Radiopharmaceuticals. Dependence on Aqueous Solution Reaction Conditions

Abstract: We study Re analogues of 99mTc renal agents to interpret previous results at the 99mTc tracer level. The relative propensities of amine donors vs. carboxylate oxygen donors of four L = polyaminocarboxylate ligands to coordinate in fac-[ReI(CO)3L]n complexes were assessed by examining the reaction of fac-[ReI(CO)3(H2O)3]+ under conditions differing in acidity and temperature. All four L [N,N-bis-(2-aminoethyl)glycine (DTGH), N,N-ethylenediaminediacetic acid, diethylenetriamine-N-malonic acid, and diethylenetria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 64 publications
(226 reference statements)
5
54
0
Order By: Relevance
“…The low reactivity of the alcohols tested versus the amines that were tested previously suggests that selective bioconjugation to the fac-{ 99m Tc(CO) 3 } + core through an amidine linkage is feasible for biomolecules that have both amine and hydroxy groups. Finally, a comparison of the CϵN bond lengths that were obtained for the fac-[Re(CO) 3 (CH 3 CN) 3 ]BF 4 /PF 6 complexes with those values obtained for other rhenium acetonitrile complexes revealed that there is no significant difference between the CϵN bond lengths and that there is no correlation to the acetonitrile reactivity. It is possible that the fac-{Re(CO) 3 } + core stabilizes the transition state for amine or alcohol addition.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The low reactivity of the alcohols tested versus the amines that were tested previously suggests that selective bioconjugation to the fac-{ 99m Tc(CO) 3 } + core through an amidine linkage is feasible for biomolecules that have both amine and hydroxy groups. Finally, a comparison of the CϵN bond lengths that were obtained for the fac-[Re(CO) 3 (CH 3 CN) 3 ]BF 4 /PF 6 complexes with those values obtained for other rhenium acetonitrile complexes revealed that there is no significant difference between the CϵN bond lengths and that there is no correlation to the acetonitrile reactivity. It is possible that the fac-{Re(CO) 3 } + core stabilizes the transition state for amine or alcohol addition.…”
Section: Introductionmentioning
confidence: 99%
“…Our primary aim in the investigation of the synthesis and properties of complexes with a fac-{Re(CO) 3 } + core is the development of renal imaging agents with a fac-{ 99m Tc-(CO) 3 } + core. [1][2][3] This approach has led to the development of fac-{ 99m Tc(CO) 3 } + renal agents that have shown promising pharmacokinetic properties in humans.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations